Diabetes fatalism and its emotional distress subscale are independent predictors of glycemic control among Lebanese patients with type 2 diabetes - Bassil, Maya (2017)
Background: Achieving and sustaining optimal glycemic control in type 2 diabetes (T2DM) is difficult because of socio-cultural and psychosocial factors including diabetes fatalism. Diabetes fatalism is ‘a complex psychological cycle characterized by perceptions of despair, hopelessness, and powerlessness’. Purpose: The purpose of this paper is to explore whether diabetes fatalism and other psychosocial and socio-cultural variables are correlates of glycemic control in Lebanese population with T2DM. Methods: A convenience sample of 280 adult participants with T2DM were recruited from a major hospital in greater Beirut-Lebanon area and from the community. Diabetes fatalism was assessed using the Arabic version of 12-item Diabetes Fatalism Scale. Multiple linear regression models were used to assess the relationship between HbA1c and psychosocial and socio-cultural characteristics including diabetes fatalism. Four models were run to examine the independent association between HbA1c and diabetes fatalism and to identify which of the 3 subscales (emotional distress, spiritual coping and perceived self-efficacy) were associated with HbA1c. Results: The mean age of the participants was 58.24(SD = 13.48) and the majority were females (53.76%), while 32.73% of the sample had diabetes for more than 10 years. Fully adjusted multiple linear regression models showed that higher scores on diabetes fatalism and the emotional distress subscale (P = 0.018) were significantly associated with higher HbA1c values. In addition, having diabetes for more than 11 years (P = 0.05) and a higher number of diabetes complications (P < 0.001) were associated with higher HbA1c levels. However, advanced age (P = 0.055), female gender (P = 0.003), and diabetes education (P = 0.011) were significantly associated with lower HbA1c levels. Conclusion: This is the first study in the Arab region that identifies diabetes fatalism as an independent predictor of glycemic control among Lebanese. Future studies should further investigate this construct to guide interventions that can address it for better diabetes outcomes.